Ferrocarriles hacia el Oriente. Articulación del territorio y construcción nacional a inicios del siglo XX en el Ecuador (Estudios) - Esvertit Cobes, Natália (2015)
The railway lines proyect to the Eastern provinces of Ecuador that was established in the process of nation building at the beginning of the 20th Century formed an integral part of the program promoted by the liberal governmentes, that had intrest in articulating the region and control of the amazonic space. There is an analysis on the debate about the constrution of roads to the East at the beginning of Century and the development a railines to the cities of Ambato to Curaray, also sketching other railroad proyects to the East. The study contributes to redeeming the history of one of the raillines that has ocuppied significat political debates in the period and to situated some of the contradictions that were presented in the process of nation building.